Mental health issues in athletes : symptom of stress, anxiety, depression and burnout - Ásgerður Ragnarsdóttir 1989- (2022)
Lokaður til.10.02.2024 Abstract Background: Research on mental health issues in athletes has grown significantly in the past decade. However, few comparative studies between athletes and the general population exists. Due to high physical and mental load in competitive sports, athlete burnout is an especially relevant mental health issue in athletes. Several factors, both sport specific and psychological, can increase burnout, however, no studies to-date have explored this topic among Icelandic athletes. Aim: was to identify differences in common mental disorders in non-injured athletes, injured athletes, and the general population. Also, to explore the relationship between sport-specific and psychological factors and burnout symptoms in athletes. Participants: were 84 team sport athletes (57.1% men, 18-41 years, Mage=22.9,SD=4.99) and 188 from the general population (panel) (67% women, 20-45 years, Mage=35.46,sf=5.9) from Northeast of Iceland. A questionnaire was sent out where participants were asked about e.g., injuries, sport specific factors and mental health. Results: Kruskal Wallis test showed that non-injured athletes scored lower than the panel in depressive (p=> .001), anxiety (p=>.001) and stress (p=.01) symptoms. Injured athletes also scored lower than the panel in depressive (p=.014), anxiety (p=.012) and stress (P=.004) symptoms. Correlation test showed that competing injured, having a recurrent injury, having a poor relationship with the coach, and higher levels of mental health issues increased athletes’ burnout symptoms. Conclusion: Athletes in Northeast of Iceland showed less symptoms of anxiety, depressive and stress symptoms than the panel. Results concerning burnout symptoms in athletes indicated that it may be important for athletes to get the rest and help they need before returning to competition after an injury. A good relationship between athletes and coaches is important. Therefore, it is important to educate coaches and athletes on good communication and mental health issues. ...